Pembangunan perkampungan masyarakat Asli Dayak Meratus: kajian kes di Kabupaten Hulu Sungai Tengah Povinsi Kalimantan Selatan - Baderun, Nurul Azkar (2021)
The community of Dayak Meratus comes from the South Kalimantan Province where his life was marginalized. This issue is interesting to study in order to gain a complete understanding of the public policy of the existence of indigenous Dayak Meratus along with their traditional values and beliefs. The objective of this study was, first, to identify the situation of the Meratus mountainous region which is the location of the Dayak Meratus native community in the Central Hulu River District. Second, identify the social, cultural, economic, and traditional role of the native Dayak Meratus community in the Central Hulu River District in shaping the behavior and actions of individuals in the community. Third, find out the objectives and form of development programs undertaken by the government to build the village of Dayak Meratus in Central Hulu River District. And fourth, identify the relationship between government-created development programs and social change in the Dayak Meratus community in Central Hulu River District. The methodology used in this study was qualitative. The results of this study show that the public policies of the New Order government based on modernization ignore the native Dayak Meratus people because they lived in the forest. Although their traditional values and beliefs do not conflict with modernity. They were allowed to live in seclusion in the forest, while forests were left to the company to be used for foreign exchange. During the period of reform, local governments began implementing a solution restructuring program, providing basic education and health services, which they received openly. Through an analysis of the integration of regional physical conditions, values and traditional beliefs, a model for the development of native Meratus Dayak villages will be developed, focusing on human resource development supported by settlement programs, transportation facilities, basic education services, health services and economic development according to the natural environment of Mount Meratus to maintain their sustainability.